Single-Step Transepithelial PRK vs Alcohol-Assisted PRK in Myopia and Compound Myopic Astigmatism Correction. Issue 6 (February 2016) - Kaluzny, Bartlomiej J.; Cieslinska, Iwona; Mosquera, Samuel A.; Verma, Shwetabh
Abstract : Abstract: Transepithelial photorefractive keratectomy (tPRK), where both the epithelium and stroma are removed in a single-step, is a relatively new procedure of laser refractive error correction. This study compares the 3-month results of myopia and compound myopic astigmatism correction by tPRK or conventional alcohol-assisted PRK (aaPRK). This prospective, nonrandomized, case–control study recruited 148 consecutive patients; 93 underwent tPRK (173 eyes) and 55 aaPRK (103 eyes). Refractive results, predictability, safety, and efficacy were evaluated during the 3-month follow-up. The main outcome measures were uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), and mean refractive spherical equivalent (MRSE). Mean preoperative MRSE was −4.30 ± 1.72 D and −4.33 ± 1.96 D, respectively ( P  = 0.87). The 3-month follow-up rate was 82.1% in the tPRK group (n = 145) and 86.4% in aaPRK group (n = 90), P  = 0.81. Postoperative UDVA was 20/20 or better in 97% and 94% of eyes, respectively ( P  = 0.45). In the tPRK and aaPRK groups, respectively, 13% and 21% of eyes lost 1 line of CDVA, and 30% and 31% gained 1 or 2 lines ( P  = 0.48). Mean postoperative MRSE was −0.14 ± 0.26 D in the tPRK group and −0.12 ± 0.20 D in the aaPRK group ( P  = 0.9). The correlation between attempted versus achieved MRSE was equally high in both groups. Single-step transepithelial PRK and conventional PRK provide very similar results 3 months postoperatively. These procedures are predictable, effective, and safe for correction of myopia and compound myopic astigmatism.